2005
DOI: 10.1111/j.1601-0825.2005.01105_52.x
|View full text |Cite
|
Sign up to set email alerts
|

P29 
The effects of essential oils on periodontopathic bacteria and oral halitosis

Abstract: Oral halitosis has been associated with periodontal disease. Hydrogen sulphide, methyl mercaptan and dimethyl sulphide are the major components of halitosis originating in the oral cavity. These compounds are mainly produced by periodontopathic bacteria in the oral cavity. In the absence of the bacteria, the odoriferous compounds are not generated. We have demonstrated the antibacterial effects of essential oils on the periodontopathic bacteria such as Porphyromonas gingivalis, Actinobacillus actinomycetemcomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…For example, the soluble components in water of TTO can inhibit the production of lipopolysaccharide induced by inflammatory mediators which Tumor Necrosis Factor (TNF), interleukin-1 (IL-1), IL-10 and prostaglandin E2 (22). Saxer et al (23) have shown that the 'action of the main components of TTO, 1,8-cineol and terpinen-4-ol, as well as lead to a reduction in inflammation of the oral tissues, also means less plaque formation' as reported by Takarada et al, which demonstrated that TTO is able to inhibit the adhesion of S. mutans and Porphyromonas gingivalis (24). Therefore, the TTO can have a role in the treat- original research article ment of gingivitis and oral candidiasis (24)(25)(26) and there are also some preliminary evidences to suggest the reduction of levels of different compounds associated with bad breath (27).…”
Section: Biological Propertiesmentioning
confidence: 73%
“…For example, the soluble components in water of TTO can inhibit the production of lipopolysaccharide induced by inflammatory mediators which Tumor Necrosis Factor (TNF), interleukin-1 (IL-1), IL-10 and prostaglandin E2 (22). Saxer et al (23) have shown that the 'action of the main components of TTO, 1,8-cineol and terpinen-4-ol, as well as lead to a reduction in inflammation of the oral tissues, also means less plaque formation' as reported by Takarada et al, which demonstrated that TTO is able to inhibit the adhesion of S. mutans and Porphyromonas gingivalis (24). Therefore, the TTO can have a role in the treat- original research article ment of gingivitis and oral candidiasis (24)(25)(26) and there are also some preliminary evidences to suggest the reduction of levels of different compounds associated with bad breath (27).…”
Section: Biological Propertiesmentioning
confidence: 73%
“…Terpinen-4-ol (30-40%) γ-Terpinene (10-28%) α-Terpinene (5-13%) 1,8-Cineol (5-15%) Terpinolene (1.5-5%) p-Cymene (0.5-12%) α-Pinene (1-6%) α-Terpineol (2-8%) Aromadendrene (traces-7%) Hammer et al, 1996;Shapiro et al, 1994;Hammer et al, 2003b;Griffin et al, 2000;Hammer et al, 1999;Hammer et al, 2002;Christoph et al, 2000;Banes-Marshall et al, 2001;Nelson, 1997;Nenoff et al, 1996;Oliva et al, 2003;Carson et al, 1995Carson et al, , 1996Carson and Riley, 1994;Brophy et al, 1989;D'Auria et al, 2001;Elsom and Hide, 1999;Gustafson et al, 1998;Hammer et al, 2003a;Mann and Markham, 1998;Mondello et al, 2003;Raman et al, 1995;Sherry et al, 2001;…”
Section: Australiamentioning
confidence: 99%
“…These studies indicate that although TTO may cause decreases in the levels of oral bacteria, this does not necessarily equate to reduced plaque levels. However, TTO may have a role in the treatment of gingivitis, and there is also some evidence preliminary suggesting that TTO reduces the levels of several compounds associated with halitosis (144).…”
Section: Clinical Efficacymentioning
confidence: 99%